PENGARUH PROGRAM WEEKEND LIST DI NET. TERHADAP KOMUNITAS SANGGAR SENAM DAMAI LINE DANCE DALAM MENGHABISKAN WAKTU LUANG: THE EFFECT OF "WEEKEND LIST" PROGRAMS IN NET. TOWARDS A COMMUNITY OF "DAMAI" LINE DANCE COMMUNITY IN SPENDING TIME - Wijayanti, Anastasia Rosi; Utami, Citra Dewi (JURNAL KOMUNITAS, 2022)
This research is motivated by the existence of the Weekend List program that affects the lifestyle of members of the Damai Line Dance gym. The theory used in this research is consumer culture. The research method is descriptive qualitative, data collection through observation, interviews, and Focused Group Discussion (FGD). The results showed that the Weekend List event affected the members of the Damai Line Dance community, this can be seen from the lifestyle that originally never planned for traveling to become routine for traveling together with references they got from the Weekend List shows. The main data is generated from the informants' utterances and secondary data from the program video. Based on the results of these studies indicate that there are factors that affect the audience, namely cultural, social, personal and psychological factors. The audience expressed the appearance of a stylist host and was able to convey the message well so that it could be received by the audience. The audience also stated that the tourist attractions and eating places visited were very interesting, instagramable and popular.